Inhibition of Juice Komba-Komba (Chromolaenaodorata) Leaf Against Growth of Bacteria Staphylococcus aureus - Reni Yunus; Muhammad Hilam; Satya Darmayani (International Journal of Applied Biology, 2019)
Nowadays many plants can be used as traditional medicines to overcome various diseases including infections, because the use of traditional medicines is relatively safer compared to drugs derived from chemicals. One of the local plants in Southeast Sulawesi that has been empirically used as a medicine for wounds is a race of plants. Komba-komba leaves (Chromolaena odorata) containcompounds alkaloid, flavonoids, tannins, phenols, triterpenoids, saponins and steroids which have their respective functions in inhibiting the growth of microorganisms or antibacterial. This study aims to determine the inhibition of komba-komba leaf extract (Chromolaena odorata) on the growth ofbacteria Staphylococcus aureus. This type of research is experimental laboratories. The method used was agar diffusion with 5 treatment concentrations, namely komba-sheep leaf extract concentration (Chromolaena odorata) 20%, 40%, 60%, 80% and 100%, positive control (tetracycline) and negative control (aquadest) and repetition . The results showed that there was a inhibition zone of komba-komba leaf extract (Chromolaena odorata) on the growth ofbacteria Staphylococcus aureus at a concentration of 20% at 2 mm, a concentration of 40% at 3.7 mm, a concentration of 60% at 4.7 mm, a concentration of 80% 6.2 mm and a concentration of 100% by 8 mm.